Leadless left bundle branch pacing: feasibility in an animal model. (19th May 2022) - Vergara, P; Taloni, ST; Shute, AS; Lee, ML
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): EBR Systems Inc. Introduction: Epicardial cardiac resynchronization therapy (CRT) is an established treatment for heart failure; left bundle branch (LBB) pacing has been proposed to overcome epicardial CRT limitations. In this study, we report on the first implants of a leadless electrode for endocardial pacing of the LBB in a porcine model. Methods: The implant of the leadless, left ventricular endocardial pacing system (WiSE-CRT System) was attempted by transeptal approach in two porcines. Fluoroscopic and transoesophageal echocardiographic guidance were used to navigate the Delivery Sheath to the LBB area; the targeted implant site was selected by analysis of the electrograms from the implanting Electrode. At the end of the procedure, the animals were sacrificed and the hearts were isolated and analysed. Results: In both animals, the Delivery System was successfully navigated to the LV septum. The target sites showed LBB electrograms preceding the far field ventricular electrogram by 15ms. The Electrode was successfully implanted on both animals with pacing threshold <2.0V @ 0.5ms. The implant of the pacing electrode was associated with minimal, multifocal haemorrhage; Purkinje fibers components of the LBB were observed in the on both sides of the site of implantation site. The lesion was 1.7 mm large and 2 mm deep. Conclusions: This study supports the feasibility of leadless LBB pacing. Anatomical evaluation showed a close relationship between the Electrode and the LBB, with absence of significant damage to the conduction system from the implanted Electrode.